Advanced wireless networks : technology and business models - Glisic, Savo G. (Chichester, West Sussex, United Kingdom : Wiley, 2016)
Covering the status of wireless networks and their future potential as the industry prepares for 4G, this work adopts a logical approach, beginning each chapter with introductory material, before proceeding to more advanced topics and tools for system analysis.
Includes bibliographical references and index.
Online resource; title from PDF title page (John Wiley, viewed June 1, 2016).
Keywords: Wireless communication systems; Electronic books